Indonesian to English Translation Strategies Used in Webtoon “My Pre-Wedding" - Istiqomah, Lilik; Khasanah, Darojatin; Tauhida, Aisyana; Ningtyas , Ristina Ayu; Rohimah, Anisa Nur (Elsya : Journal of English Language Studies, 2020)
This paper maps the Indonesian-English translation strategies within a comic published in Webtoon, arguably the most popular global digital comic service platform in this generation. The data was taken from Webtoon. The data is an Indonesian Webtoon entitled “My Pre-Wedding” created by Annisa Nisfihani and its translation into English by Pujangga Team. This study’s design is qualitative, primarily describing the data by way of document review. Researchers catagorised the data into six translation strategies as stated by Baker Mona (1992). The researchers accumulated 261 data of translation strategies. Based on the analysis undertaken, the translation strategies used are mainly general word (17 findings = 6.5%), cultural substitution (47 findings = 18%), loan word (16 findings = 6.1%), paraphrase using a related word (53 findings = 20.3%), paraphrase using unrelated words (63 findings = 24.1%), and omission (65 findings = 24.9%). The results not only contribute to the research on language translation strategies, but also give insight on how they apply within the new generation’s smartphone cyberculture.